KRITIK MITOS TENTANG â€œHANG TUAHâ€ KARYA AMIR HAMZAH - Santosa, Puji (ATAVISME, 2014)
This study reveals the myth criticism on rhyme "Hang Tuah", an Amir Hamzah?s work expressing Malay myth. The Malay myth found in the rhyme "Hang Tuah" is placed as a meeting place of myth criticism study which includes (1) the structure of the text, (2) figure with its ideology, (3) setting presenting the myth, (4) type of myth, (5) method the poet displays the myth, and (6) the benefit or function of myth. The six elements of the review are expected to contribute in exposing and describing the element of mythology in modern Indonesian poetry and its relevance to the present situation. It is identified that Hang Tuah has an ideology of Malay heroism loyalty able to be a resource in national character building: willing to sacrifice and resilient in defending the country's sovereignty rights. The Malay heroic myth of Hang Tuah, delivered in the form of poetic ballads, adds to the classic aesthetic value. The present benefits of Hang Tuah myth, by his heroism in getting rid of European colonization, is certainly to boost the fighting spirit in defending the rights and dignity as an independent nation, free from occupation or colonialism.  This study reveals the myth criticism on rhyme "Hang Tuah", an Amir Hamzah?s work expressing Malay myth. The Malay myth found in the rhyme "Hang Tuah" is placed as a meeting place of myth criticism study which includes (1) the structure of the text, (2) figure with its ideology, (3) setting presenting the myth, (4) type of myth, (5) method the poet displays the myth, and (6) the benefit or function of myth. The six elements of the review are expected to contribute in exposing and describing the element of mythology in modern Indonesian poetry and its relevance to the present situation. It is identified that Hang Tuah has an ideology of Malay heroism loyalty able to be a resource in national character building: willing to sacrifice and resilient in defending the country's sovereignty rights. The Malay heroic myth of Hang Tuah, delivered in the form of poetic ballads, adds to the classic aesthetic value. The present benefits of Hang Tuah myth, by his heroism in getting rid of European colonization, is certainly to boost the fighting spirit in defending the rights and dignity as an independent nation, free from occupation or colonialism Key Words: myth criticism; heroism; loyalty; fighting spirit Abstrak: Penelitian ini mengungkapkan kritik mitos sajak ?Hang Tuah? karya Amir Hamzah yang menampilkan mitos Kemelayuan. Mitos Kemelayuan yang ditemukan dalam sajak ?Hang Tuah? tersebut ditempatkan sebagai pumpunan penelaahan kritik mitos yang meliputi (1) struktur teks, (2) tokoh dengan ideologinya, (3) latar yang menghadirkan mitos, (4) jenis mitos, (5) cara penyair menampilkan mitos, dan (6) manfaat atau fungsi mitos. Dengan keenam unsur penelaahan kritik mitos itu diharapkan dapat diungkapkan dan dideskripsikan adanya unsur mitologi dalam puisi Indonesia modern dan relevansinya dengan keadaan masa kini. Ternyata Hang Tuah memiliki ideologi loyalitas heroisme Kemelayuan yang dapat menjadi pembentuk karakter bangsa: rela berkorban dan tangguh mempertahankan hak kedaulatan negeri. Mitos kepahlawanan Melayu Hang Tuah dengan cara disampaikan dalam bentuk balada yang puitis menambah nilai estetika klasik. Manfaat bagi kehidupan masa kini mitos Hang Tuah, atas kepahlawanannya mengusir penjajahan bangsa Eropa, tentu sebagai pemompa semangat juang mempertahankan hak dan martabat diri sebagai bangsa yang merdeka, bebas dari penjajahan atau kolonialisme